Developing a new concept of Chinese packaging design inspired by MUJI’s characters - Wang, Hang (2023)
In the modern competitive market, packaging is the first impression that can attract the consumers. Effective packaging design must clearly convey the product's value and unique selling points while differentiating from other similar brand products. Increasingly, the trend of integrating cultural elements into modern packaging design is gaining popularity. This research aims to develop a new concept of Chinese packaging design inspired by MUJI's characters. A comprehensive analysis of existing literature focused on the traditional cultural elements and modern design philosophies that can contribute into a new market competitive. While the quantitative method was employed to obtain the primary data through survey by questionnaire. The questionnaire was designed specifically to evaluate the MUJI’s characters design from the design experts and the MUJI representatives. While the empirical analysis by sampling design is used to validate the new concept of Chinese packaging design through the users. The results acknowledged fifteen MUJI's design characters that can be inspired a new development of Chinese packaging design. A new concept of Chinese packaging design was introduced inspire by the MUJI’s characters toward better value and aesthetic appearance as well as its probability to enhance the economic growth of China’s packaging industry.